Who will take care of us when we get old? - Helena Akemi Wada Watanabe; Yeda Aparecida de Oliveira Duarte; Karla Cristina Giacomin; Ana Amélia Camarano (Brazilian Society of Geriatrics and Gerontology, 2023)
None.